Pressure drop correlation for oil-refrigerant R134a mixture flashing flow in a small diameter tube - Castro, Heryca O. S.; Gasche, Jose Luiz [UNESP]; Prata, Alvaro T. (Elsevier B.V., 2009)
This paper presents an experimental investigation of the ester oil ISO VG10/refrigerant R134a mixture flashing flow in a 6.0 m long, 3.22 mm ID tube, which is one of the primary steps towards the construction of a methodology for the study of the lubrication and gas leakage in refrigeration compressors. The phase change starts with solubility reduction of the refrigerant in the oil as the pressure decreases due to the friction forces. in this flashing flow the foam pattern is observed at the end of the tube as vapor quality reaches high values, and this is a particular phenomenon of this kind of mixture flow. In order to study this pressure drop, an experimental apparatus was designed to allow the measurement of both pressure and temperature profiles along the tube as well as the visualization of the flow patterns. Pressure and temperature distribution along the flow were measured for saturation pressure ranging from 450 to 650 kPa, mass flux ranging from about 2000 to 3000 kg/(m(2)s), temperatures around 303 K, and inlet refrigerant concentration varying between 0.2 and 0.4 kg ref/kg mixt. An available correlation proposed to predict the frictional pressure drop for a mixture composed by the mineral oil SUNISO 1GS and refrigerant R12 flowing in small diameter tubes yielded large deviations in predicting the ester oil and refrigerant R134a mixture flow. A new correlation has been proposed that fitted the experimental data with rms deviations of 24%. (C) 2008 Elsevier Ltd and IIR. All rights reserved.
Keywords: Refrigeration system; Mixture; R134a; Synthetic oil; Two-phase flow; Tube; Geometry; Experiment; Pressure drop; Correlation